A system for management and analysis of rice genomics data for candidate gene discovery - Mansueto, Locedie A. (2005)
An information system to manage and analyze rice genomics data was developed to facilitate discovery of gene functions following the candidate gene strategy. All predicted genes in the rice genome were analyzed using tools to assign putative functions, chromosomal position and expression to treatments. Various biological (QTL, biopathways, germplasm, treatment) and molecular (gene expression, protein-protein interaction, transcriptional regulation, metabolic reactions) evidence of gene activity were used to constrain the gene set. A domain, schema and store independent middleware platform was developed to integrate these data. New evidence can easily be added by mapping API functions or relational queries as modules. An interactive and flexible client application queries the system then performs set operations and use-case computation in the domain's logic. The system was applied to experimental data generated by our collaborators at the International Rice Research Institute and from public domain databases to identify candidate genes and pathways for drought tolerance in rice.